2017
DOI: 10.15171/ijtmgh.2017.10
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinations of International Travellers From Greece to Sub-Saharan Africa

Abstract: Introduction During that past few decades, international travel has dramatically increased worldwide. The number of international tourists is expected to reach a total of 1.6 billion by the year 2020. Travel to Africa recorded a growth of 2%. 1 International travels to tropical and subtropical countries may increase the risk of exposure to infectious diseases and may facilitate their global spread. 2,3 Sub-Saharan Africa is one of the most common destinations (26.7%) where illnesses are acquired by travellers.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…4 These vaccines require a longer time for the entire schedule to be administered. 4 A study among international travellers to Sub-Sahara Africa by Pavli et al 28 showed lower rates of vaccination for typhoid, hepatitis A, and tetanus toxoid than seen in the present study, in which vaccination rates were reported to be 76.7%, 72.1%, and 58.1%, respectively (Table 3). This may be explained by the origin of travelers from the United States, United Kingdom, and Europe where travel clinics are well established and travelers are better informed.…”
Section: Discussioncontrasting
confidence: 52%
“…4 These vaccines require a longer time for the entire schedule to be administered. 4 A study among international travellers to Sub-Sahara Africa by Pavli et al 28 showed lower rates of vaccination for typhoid, hepatitis A, and tetanus toxoid than seen in the present study, in which vaccination rates were reported to be 76.7%, 72.1%, and 58.1%, respectively (Table 3). This may be explained by the origin of travelers from the United States, United Kingdom, and Europe where travel clinics are well established and travelers are better informed.…”
Section: Discussioncontrasting
confidence: 52%